The Scaled SLW model of gas radiation in non-uniform media based on Planck-weighted moments of gas absorption cross-section. (February 2018) - Solovjov, Vladimir P.; Andre, Frederic; Lemonnier, Denis; Webb, Brent W.
Highlights: The Scaled SLW model for prediction of radiation transfer in non-uniform gaseous media is presented. The moments of gas absorption cross-section weighted by the Planck blackbody emissive power are used for construction of scaled model. The first moment – Planck mean, and minus first moment – Rosseland mean of absorption cross-section are applied for calculation of the scaling coefficient. The scaling coefficient is calculated explicitly. The tabulated ALBDF calculated from the HITEMP-2010 is used in spectral calculations. Abstract: The Scaled SLW model for prediction of radiation transfer in non-uniform gaseous media is presented. The paper considers a new approach for construction of a Scaled SLW model. In order to maintain the SLW method as a simple and computationally efficient engineering method special attention is paid to explicit non-iterative methods of calculation of the scaling coefficient. The moments of gas absorption cross-section weighted by the Planck blackbody emissive power (in particular, the first moment – Planck mean, and first inverse moment – Rosseland mean) are used as the total characteristics of the absorption spectrum to be preserved by scaling. Generalized SLW modelling using these moments including both discrete gray gases and the continuous formulation is presented. Application of line-by-line look-up table for corresponding ALBDF and inverse ALBDF distribution functions (such that no solution of implicit equations is needed) ensures that the method is flexible and efficient. Predictions for radiative transfer using the Scaled SLW model are compared to line-by-line benchmark solutions, and predictions using the Rank Correlated SLW model and SLW Reference Approach. Conclusions and recommendations regarding application of the Scaled SLW model are made.